TINDAKAN KEBIRI KIMIAWI TERHADAP PELAKU KEKERASAN SEKSUAL ANAK DAN KAITANNYA DENGAN TENAGA MEDIS - Ni Komang Ratih Kumala Dewi (Fakultas Hukum Universitas Dwijendra, 2021)
The crime of sexual violence is a crime against society, especially children. In order to protect children's growth and development, the government issued Law Number 27 of 2016, to impose additional sanctions in the form of chemical castration. There is a principle conflict in the imposition of castration sanctions for medical personnel who will become executors, on the one hand carrying out orders from statutory regulations and court decisions, on the other hand medical personnel have the principle of healing and respecting human life naturally in accordance with the professional oath. The purpose of this study is to determine the regulation of castration sanctions and to know the basis for the actions of medical personnel, the method used is normative legal research. The results of his research on the regulation of castration sanctions are regulated in the provisions of Article 81 paragraph 7 of Law No. 27 of 2016 and Government Regulation number 70 of 2020, then Government Regulation Number 77 of 2020 becomes the basis for implementation guidelines which in the provisions provide legitimacy and orders to medical personnel and psychiatrists to carry out the task of providing chemical castration based on justice.